If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5=-3-1/9x
We move all terms to the left:
5-(-3-1/9x)=0
Domain of the equation: 9x)!=0We add all the numbers together, and all the variables
x!=0/1
x!=0
x∈R
-(-1/9x-3)+5=0
We get rid of parentheses
1/9x+3+5=0
We multiply all the terms by the denominator
3*9x+5*9x+1=0
Wy multiply elements
27x+45x+1=0
We add all the numbers together, and all the variables
72x+1=0
We move all terms containing x to the left, all other terms to the right
72x=-1
x=-1/72
x=-1/72
| x-6/12=40 | | 7/3x+(-3)=4 | | 3x-5x-7=-2x+5-7 | | 3=1/2y | | 25=-5+2/3m | | y+1116=4 | | 12x-24x=-36x | | 1.8x=1.5x+18.72 | | x/8-17=7 | | 12x-24x=36x | | .6x+9=7x-5 | | -3-1/4x=9 | | 3g=-7 | | 9y+3=180 | | 7x+2=-35 | | -0.54=00.4h | | -5x+2(-5x-10)=-50 | | 4y-2°=21° | | (–17––14)×(10+18÷–9)=a | | -2x-16=-5(x+5) | | 3x+18+4x+15=180° | | 9+3y=180 | | 9.76–5.15x+(–10.85x)=8.76–11 | | 51+3y=180 | | 3x+12=5x-60 | | a/30=14 | | 6(6x+5)=36x+30 | | |4x+12|+5=21 | | -6(x+3)=-8x-36 | | 3^5x=9^2 | | (3x−9)+(x+3)=180 | | 7x+9=5+15 |